2014
DOI: 10.1093/toxsci/kfu154
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy in Usnic Acid-Induced Toxicity in Hepatic Cells

Abstract: The use of usnic acid and usnic acid-containing products is associated with acute liver failure; however, mechanistic studies of hepatotoxicity caused by usnic acid are limited. In this study, we investigated and characterized the possible mechanisms, especially the role of autophagy in usnic acid's toxicity in human HepG2 cells. Usnic acid caused apoptosis as demonstrated by an increased caspase-3/7 activity and an increased subdiploid nucleus formation. Usnic acid-induced autophagy as demonstrated by the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 50 publications
8
43
0
Order By: Relevance
“…Increased accumulation in S phase could be attributed to an increase in cells that are actively replicating DNA; however, this may not be the case for usnic acid treatment. Our previous report showed that usnic acid inhibited cell proliferation (Chen et al 2014a), and our current results show that usnic acid reduces the expression of key cyclin-related proteins that are critical for S phase progression, as indicated in Fig. 2.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Increased accumulation in S phase could be attributed to an increase in cells that are actively replicating DNA; however, this may not be the case for usnic acid treatment. Our previous report showed that usnic acid inhibited cell proliferation (Chen et al 2014a), and our current results show that usnic acid reduces the expression of key cyclin-related proteins that are critical for S phase progression, as indicated in Fig. 2.…”
Section: Resultssupporting
confidence: 79%
“…Although different sensitivities were observed in distinct cells, we obtained similar toxicity results with multiple endpoints. Our mechanistic studies in HepG2 cells revealed that various signaling pathways were affected by usnic acid (Chen et al 2014a, 2015). In this study, we continued to use this cell line, not only because the liver is the primary target organ for usnic acid’s toxicity (Guo et al 2008), but also the feasibility and capability of HepG2 cells for genetic modifications (silencing genes of interest in this study) enabled us to elucidate in-depth molecular mechanisms (Chen et al 2014a).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations